Treatment patterns, outcomes, healthcare resource utilization, and costs associated with locally advanced squamous cell carcinoma of the head and neck in Japan - Nibu, Kenichi; Tahara, Makoto; Yoshimi, Noriko; Argoubi, Ramzi; Rascon-Velasco, Vanessa; Rahshenas, Makan; Bobiak, Sarah; Lu, Ember (Frontiers in Oncology, 2025)
ObjectiveTreatment patterns and healthcare resource utilization (HCRU) data in patients with locally advanced (stage III to IVB) squamous cell carcinoma of the head and neck (LA SCCHN) in Japan are limited. This study describes the patient demographics and characteristics, treatment patterns, HCRU, and costs among Japanese patients with newly diagnosed LA SCCHN.MethodsThis longitudinal, observational, retrospective study was conducted using real-world medical claims data from the Medical Data Vision Co., Ltd. database in Japan (1 January 2015–31 July 2022). Patients aged ≥18 years at the index date (first date of locally advanced head and neck cancer [HNC] diagnosis) and having a confirmed diagnosis of HNC during 01 January 2016–30 June 2021 in the oral cavity, larynx, hypopharynx, or oropharynx (based on ICD-10 diagnostic codes) were included. Baseline demographic and clinical characteristics were collected during the pre-index period. Treatment patterns, HCRU, and associated costs were reported during the post-index period.ResultsOf the included 6741 patients with LA SCCHN, 51.3% received definitive nonsurgical treatment, 32.4% underwent primary resection, and 16.1% did not receive any agent. The most common chemotherapy agent used for chemoradiotherapy was cisplatin (74.7%). Docetaxel, cisplatin, and 5-fluorouracil combination (TPF) was used as induction chemotherapy for 28.6% of patients who received induction treatment followed by surgery and in 55.6% of patients who received induction treatment followed by radiotherapy. Patients receiving primary resection were typically older than those receiving definitive nonsurgical treatment for each cancer site and stage. Almost all patients had ≥1 all-cause hospitalizations with substantial HCRU-associated costs.ConclusionsThis real-world study demonstrates that treatment of patients with LA SCCHN in Japan often included definitive nonsurgical treatment or primary surgery. The substantial burden related to LA SCCHN-associated HCRU and considerable percentage of patients receiving no treatment highlights a need for novel and effective therapies for LA SCCHN.